2008
DOI: 10.1007/s11119-008-9052-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping subsoil acidity and shallow soil across a field with information from yield maps, geophysical sensing and the grower

Abstract: Management decisions, such as subsoil liming or varying fertilizer inputs to take account of soil depth and anticipated yields require knowledge of where subsoil constraints to root growth occur across the field. We used selected yield maps based on criteria derived from crop simulation, apparent soil electrical conductivity (EC a ), gammaray emission maps and a soil type map drawn by the grower to predict the spatial distribution of subsoil acidity and shallow soil across a field. Yield maps integrate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…Given that 63% of pasture, 87% of wheat, 89% of dairy soil samples appear to contain Colwell P concentrations above the CV for 90-95% of maximum production, yields are more likely to be constrained by other factors such as lack of water, soil acidity, and other nutrient deficiencies (Table 3). Practices to ameliorate many of these other constraints already exist, including (i) the application of liming materials to manage soil acidity (Snars et al 2004;Wong et al 1998;Wong et al 1995), (ii) improving water holding and P retention, and reducing Colwell P/PBI of sandy soils (Wong and Asseng 2006;Vlahos et al 1989;Summers et al 1993), (iii) relieving subsoil constraints to root growth to capture some leached P (Wong and Asseng 2007), and (iv) using techniques to identify site specific nutrient needs (Wong et al 2001(Wong et al , 2008(Wong et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Given that 63% of pasture, 87% of wheat, 89% of dairy soil samples appear to contain Colwell P concentrations above the CV for 90-95% of maximum production, yields are more likely to be constrained by other factors such as lack of water, soil acidity, and other nutrient deficiencies (Table 3). Practices to ameliorate many of these other constraints already exist, including (i) the application of liming materials to manage soil acidity (Snars et al 2004;Wong et al 1998;Wong et al 1995), (ii) improving water holding and P retention, and reducing Colwell P/PBI of sandy soils (Wong and Asseng 2006;Vlahos et al 1989;Summers et al 1993), (iii) relieving subsoil constraints to root growth to capture some leached P (Wong and Asseng 2007), and (iv) using techniques to identify site specific nutrient needs (Wong et al 2001(Wong et al , 2008(Wong et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies did not consider the size and nature of the field, which restricted the full potential knowledge of the farmers. When this restriction was not made in advance, Australian farmers indicated that there were more than three types of soil in a given field (Oliver et al 2010;Wong et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While farmer knowledge can go some way towards diagnosis of causes (Oliver et al 2010), other methods (see review by Robertson et al 2007) are under development such as some geophysical techniques (Wong et al 2008), temporal dynamics of remotely sensed NDVI (Adams and Maling 2005;Robertson et al 2007), and temporal dynamics of multiple yield maps (Lawes et al 2009). Because causes of variation are context specific, no one method is universally applicable.…”
Section: Complexitymentioning
confidence: 99%